Assessment of the potential of tourist rentals through online platforms: a case study of Melilla - Prados-Castillo, Juan F.; Fuentes Collado, Miguel; Fuentes Jiménez, Antonio Miguel (JOINETECH, 2025)
This study analyses the impact of recent public policies to promote tourism in Melilla and assesses the growth potential of the market for tourist rentals marketed through different digital platforms. A mixed methodology based on documentary analysis of institutional initiatives and empirical data from AirDNA was used. Specifically, it examines the evolution of supply, market performance, and the relative position of Melilla compared to other Spanish urban destinations. The results show that although holiday rentals in Melilla are still in their infancy, the city is highly attractive in terms of potential demand and market conditions (Market Score = 93), suggesting that there is significant room for growth in this holiday segment. At the same time, risks associated with pressure on the residential market and the need for forward planning to avoid the negative effects observed in other cities analysed in this research, such as gentrification or overtourism, are identified. The strategic dimensions of the STRATECMEL project were incorporated into the analysis, considering that it can support the competitiveness of the city's tourism. Potential factors such as digitalisation, the use of emerging technologies, and Melilla's special tax regime are highlighted. It concludes with a series of strategic recommendations aimed at a sustainable, regulated, and technologically advanced development of the city's digital tourism market.
Keywords: emerging tourism; digital holiday rentals; overtourism; emerging technologies; public policies